An Analysis of the Effect of the Social Dimensions of CSR on Corporate Image (A Study on Taman Nivea Family Care of PT Beiersdorf Indonesia) - Sri Palupi Prabandari (Brawijaya University, 2022)
The implementation of Corporate Social Responsibility (CSR) in Indonesia is stipulated in Article 74 section 4 of Law number 40 of 2007. In addition to fulfilling legal aspect, CSR can be used as a strategy to improve company’s image. The purpose of this quantitative research is to assess the effect of the social dimensions of CSR on corporate image by conducting a study on Taman Nivea Family Care, which is the CSR of PT Beiersdorf Indonesia. The sample of this research was selected using purposive sampling with the criteria of (1) people who live in Greater Malang area (Malang city, Malang regency, or Batu city), (2) people who have visited Taman Nivea Family Care, (3) people who know that Taman Nivea Family Care is the CSR program of PT Beiersdorf Indonesia. This study uses primary data obtained from questionnaires and analyzed using multiple linear regression. This study finds that the social dimensions of CSR, i.e. society, corruption, public policy, anti-competitive behavior, and compliance, significantly influence the corporate image of PT Beiersdorf Indonesia. In general, the social dimensions of CSR have 55% influence on corporate image, while the remaining 45% is influenced by other variables outside the study. This indicates that the implementation of CSR to sustainably support social life is quite relevant to improve corporate image.